Wanprestasi Dalam Perjanjian Jual Beli Motor - Hariyani Hariyani; Kairuddin Karim; Muhammad Darwis (Jurnal Litigasi Amsir, 2021)
The facts on the ground are that there are still many cases of motorbikes being confiscated and forcibly taken by the seller and/or financing. This study aims to determine the legal settlement of debtors who default. The research method used is normative legal research. with a statutory approach. This study involves literature review and documentation, followed by qualitative analysis based on primary (laws) and secondary legal materials (libraries and scientific journals). The results show that the form of settlement of the default is confiscation of vehicles by using a power of attorney to withdraw/confiscate the object of fiduciary security which has been signed by the debtor himself and the original minutes of handover to Financing employees who specifically handle withdrawals of collateral objects.